2005
DOI: 10.1111/j.1365-3024.2005.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a low protein diet on the resistance of Churra sheep to Teladorsagia circumcincta

Abstract: SUMMARY The aim of this study was to understand the influence of a low protein diet on the resistance of the Churra breed sheep to infection with Teladorsagia circumcincta. A previous experiment in our department demonstrated significant differences between resistant and susceptible sheep infected with T. circumcincta, in eggs per gram of faeces, serum pepsinogen, serum IgA and peripheral eosinophilia (unpublished). The sheep were fed with a balanced protein diet. In the current assay there were significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…Other studies have demonstrated a reduced production of eggs by gastrointestinal parasites in animals fed low-protein diets [37], [38]. A study using sheep infected with H. contortus and fed a low-protein diet showed that these animals presented more severe clinical signs than did sheep maintained with an adequate-protein diet; however, the fecal egg counts, oviposition rate and number of adult worms recovered were similar in both groups [39] …”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Other studies have demonstrated a reduced production of eggs by gastrointestinal parasites in animals fed low-protein diets [37], [38]. A study using sheep infected with H. contortus and fed a low-protein diet showed that these animals presented more severe clinical signs than did sheep maintained with an adequate-protein diet; however, the fecal egg counts, oviposition rate and number of adult worms recovered were similar in both groups [39] …”
Section: Discussionmentioning
confidence: 93%
“…In Leishmania chagasi vaccination studies using BALB/c mice fed either a control diet or a diet low in protein, iron and zinc, the vaccine efficiency was higher in the mice fed a control diet. In animals fed the deficient diet, the immune response after vaccination was much lower, and the number of parasites found in the liver and spleen was much higher compared to the control group [39]. Another study showed that sheep that are resistant or susceptible to the parasite H. contortus and fed a normal diet showed higher IgA activity compared to ewes fed a diet deficient in protein [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regards to peripheral antibody responses, findings of this experiment support the view that peripheral antibodies play a minor role in the immune response of goats towards GIN infection (Schallig et al, 1995;Coop and Kyriazakis 1999). These findings were not in agreement with previous studies in sheep that plane of nutrition may be positively correlated with antibody responses against GINs (Martínes-Valladares et al, 2005). The differences between these studies may be due to differences in the mechanisms to regulate GIN infections in sheep and goats .…”
Section: Discussioncontrasting
confidence: 99%
“…The flock and sampling month were the external factors significantly influencing all the studied traits. This reflects the importance of the management given provided to the sheep, including management practices and protein content level in the diet (Martínez-Valladares et al, 2005b), and the influence of the season as a factor directly controlling parasite development, especially in continental climates where hypobiosis phenomena are frequent (Almería et al, 1996).…”
Section: Discussionmentioning
confidence: 99%